Stress among healthcare workers during the COVID-19 pandemic and the determinant factors: a cross-sectional study (Medical Journal of Indonesia, 2022)
BACKGROUND During the COVID-19 pandemic, there has been an increase in workload, as well as greater vigilance and compliance at work. Healthcare workers must perform their duties while facing the fear of COVID-19, which can trigger and/or aggravate stress. This study aimed to obtain the determinant factors of stress among healthcare workers during the pandemic by emphasizing the change in the psychosocial situation at the hospital. METHODS This cross-sectional study was conducted from January to March 2021 using an online questionnaire consisting of personal and occupational questionnaires, as well as the validated stressor and stress questionnaires using validity and reliability tests (Cronbach’s alpha 0.8 and 0.9). For the multivariate analysis, multiple logistic regression was used to identify the determinant factors (p<0.05). Data were analyzed using SPSS software version 20 (IBM Corp., USA). RESULTS Determinant factors of the occurrence of moderate–severe stress were the alteration of stressors including age (aOR = 1.9), working hours (aOR = 1.9), work zone (aOR = 2.7), limited facilities and resources (aOR = 6.2), risk of disease transmission (aOR = 0.3), and personal work demands (aOR = 2.1). CONCLUSIONS In addition to the younger age, the determinant factors of the incidence of moderate–severe stress in healthcare workers during the COVID-19 pandemic at the hospitals were work-related conditions. However, they remained controllable to prevent stress among healthcare workers in the peak load work situations such as a pandemic.